No-Spouse Employment and the Problem of the Constitutional Court of Indonesia - YUSA, I. Gede; HERMANTO, Bagus; ARYANI, Nyoman Mas (Journal of Advanced Research in Law and Economics, 2020)
The role of Constitutional Court as the protector of human rights related with the effort to guarantee the human rights also the worker’s rights with their decision. The decision in this study related with constitutionality of no-spouse employment norms. This study aims to examine the constitutionality aspects related with no-spouse employment policy related with human rightsor worker rights. This study is using statutory approach, conceptual approach and comparative studies concerning no-spouse employment policy. The results show that no-spouse employment policy is contrary with the Constitution and human rights legal instruments. Moreover, there is problem concerning the Decision of the Constitutional Court of Indonesia on the one hand is final and binding but non-executable automatically. This study to encourage the new paradigm to ensure the execution of the Decision of the Constitutional Court of Indonesia, in this context related with decision on the constitutionality no-spouse employment norms.